Introducing Temporal Theory to the Field of Sport Psychology: Toward a Conceptual Model of Time Perspectives in Athletes’ Functioning - Stolarski, Maciej; Waleriańczyk, Wojciech; Pruszczak, Dominika (Frontiers in Psychology, 2019)
Time perspective theory provides a robust conceptual framework for analyzing human behavior in the context of time. So far, the concept has been studied and applied in multiple life domains, such as education, health, social relationships, environmental behavior, or financial behavior; however, its explanatory potential has been completely neglected within the domain of sport. In the present paper we provide a deepened theoretical analysis of the potential role of temporal framing of human experience for sport-related attitudes, emotions, and athletic performance. We propose a conceptual model in which time perspectives influence psychological functioning and performance of athletes via three major mechanisms: (1) magnitude and persistence of sport motivation and resulting athlete engagement, (2) regulation of affective states during sport performance, and (3) appraisal of one’s performance and coping with resulting emotions. We support the theoretical considerations based on the major assumptions of time perspective theory with research findings regarding the regulatory role of time perspectives in other life domains. We also highlight potential research paths that would allow us to empirically test the present model and determine the actual role of temporal perspectives in shaping crucial aspects of athletes’ psychological functioning, as well as levels of their sport performance.